Relationship satisfaction and self-esteem in patients with breast cancer and healthy women: the role of expected and actual personal projects support from the partner - Sára Imola Csuka; Judit Désfalvi; Barna Konkolÿ Thege; Viola Sallay; Tamás Martos (BMC, 2023)
Abstract Background For breast cancer patients, the partner's support for personal projects can serve as a means of adaptation. We aimed to investigate the associations between the intimate partner's personal project support and women's well-being. Methods A sample of 274 Hungarian women (breast cancer patients n = 137, control n = 137) took part in the study. Expected and actually received autonomy-, directive- and emotional project support was assessed by the procedure of Personal Project Assessment. Well-being was measured by the Relationship Assessment Scale and the Rosenberg Self-Esteem Scale. For investigating the associations between project support and well-being in a multivariate way, structural equation modelling was used. Results Except for autonomy support, participants expected more support than they received. A path model indicated multiple associations between types of project support and relationship satisfaction and self-esteem. The partner's emotional project support was predictive of women's relationship satisfaction and self-esteem, while directive support was predictive of self-esteem only. The associations showed similar patterns in the subgroups of patients with breast cancer and control. Conclusions Our results highlight the importance of involving women's subjective perspectives regarding the partner's project support while also have implications for praxis. Teaching women how to communicate their needs to their partner effectively (whether it is the need for autonomy or directive guidance) can help close the gap between expected and received support, which may in turn enhance relationship satisfaction and self-esteem.